Factors Influencing Intention to Adopt E-Wallet During Covid-19 Pandemic - Abd Razak, Siti Suraya (UUM Press, 2024)
The e-wallet feature allows consumers to make payment by transferring digital money into their virtual wallets for in-application online payments or through Quick Response (QR) codes for physical purchases. This study examines the average usage, transaction size and factors influencing the intention to adopt e-wallet among consumers during the Covid-19 pandemic. A total of 153 responses were collected and analysed using Statistical Package for Social Sciences (SPSS) to determine descriptive statistics and conduct multiple regression analysis to verify that performance expectancy, social influence, facilitating conditions, and perceived security influence the intention to use e-wallets during the Covid-19 pandemic among consumers. Performance expectancy is the strongest factor while effort expectancy is the only factor that has no influence on the intention to use e-wallets during the Covid-19 pandemic. Additionally, this study reveals that due to the current situation, consumers are pushed to adopt e-wallets despite their security concerns, and they are willing to learn to use the platforms without considering the possibilities and risks. However, the usage of e-wallets as a medium of transaction is still low due to the lack of awareness and knowledge. The outcomes of this study to provided practical contributions for policymakers and service providers on the current acceptance of e-wallets in Malaysia and to help the e-wallet industry develop more reasonable business strategies